Green Sufism Argument as Environmental Ethics (Philosophical Analysis) - Irawan, Bambang; Latif, Mohd Syahiran Abdul; Nasution , Ismail Fahmi Arrauf (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2022)
This study focuses on the Sufi thoughts in responding to the ecological crisis faced by humanity. Their responses are reflected on primary texts such as Fusus al-Hikam and Futuhat al-Makiyyah by Ibn Arabi, as well as Islamic Cosmological Doctrines by Hossein Nasr. Secondary texts include the thoughts of scholars discussing similar themes. This research employs qualitative analysis with a hermeneutic approach to interpret these texts in the context of the ecological crisis. The findings reveal that Sufi philosophy, through the theories of microcosm and macrocosm, emanation, and illumination, offers a new profound paradigm for understanding the relationship between humans and nature. This philosophy emphasizes the importance of spiritual and cosmic harmony in addressing the ecological crisis. This study contributes to scientific knowledge by integrating Sufi philosophy and ecological studies, providing a new framework to foster ecological awareness based on spirituality. These findings are relevant to the development of environmental studies grounded in spiritual and cultural values.